Development of Posters as Media to Prevent Bullying Behavior at a Junior High School in Palangka Raya - Kurniawan, Dony; Dotrimensi, Dotrimensi; Cahyaningrum, Dwi (Jurnal Lingua Idea, 2024)
This research begins with the problem of bullying behavior at a junior high school in Palangka Raya, where teachers often get complaints from students who cry because they are bullied by their friends and teachers' requests to make posters that educate students about bullying behavior. This study aims to develop posters as media to prevent bullying behavior at a junior high school in Palangka Raya. The method used in this research is RnD (Research and Development), which has steps proposed by Borg and Gall. This study uses quantitative and qualitative data to process the results of expert lecturer reviews and descriptive statistics based on a Likert scale. Data collection techniques include interviews, observations, validation sheets, and questionnaires. The results of expert lecturer validation of the material received a score of 93% with an outstanding category, and the results of expert lecturer validation of the media received a score of 86% with an excellent category. The results of product trials on 16 students get an average percentage of 85% in the very good category.